WHY IS HEALTH PROTOCOL STILL NEEDED EVEN THOUGH PEOPLE ARE GETTING VACCINATED? - Yanasta Yudo Pratama; Marwan Rosada; Elyn Arlinda (Universitas Ahmad Dahlan, 2022)
At the end of 2019, the world was rocked by a disease that spread worldwide. The disease is caused by the SARS-CoV-2 virus, also known as the Novel Corona Virus called COVID-19. This virus is responsible for many deaths; as of November 26, 2021, the total global death toll from COVID-19 was more than 5 million deaths. In July of that year, Indonesia became a country with the highest death rate and a high number of new cases, with a total of 143.796 fatalities. Making Indonesia face the problem of poor health situation.